2024
DOI: 10.1177/19458924241247107
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Nasal Nerve Ablation as a Viable Treatment Option for the Primary Symptom of Postnasal Drip

Aatin K. Dhanda,
Daniel Gorelik,
Najm Khan
et al.

Abstract: Background Postnasal drip (PND) syndrome is a prevalent complaint encountered in otolaryngology practices. PND may be refractory to medical therapy, and surgical treatments are complicated by side effects. Objective While posterior nasal nerve (PNN) ablation has demonstrated efficacy for chronic rhinitis overall, we sought to examine the effect of PNN ablation for patients with PND as their primary complaint. Methods This is a retrospective case series study of 40 chronic rhinitis (CR) patients with a primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The study by Dhanda et al discussed posterior nasal nerve (PNN) ablation as a potential treatment for chronic rhinitis (CR) patients with a primary symptom of postnasal drip (PND), often unresponsive to conventional medical therapies. 5 It presented real-world evidence outside of industry-sponsored trials which found that PNN ablation was effective in alleviating PND symptoms, especially in younger, non-smoking patients.…”
mentioning
confidence: 99%
“…The study by Dhanda et al discussed posterior nasal nerve (PNN) ablation as a potential treatment for chronic rhinitis (CR) patients with a primary symptom of postnasal drip (PND), often unresponsive to conventional medical therapies. 5 It presented real-world evidence outside of industry-sponsored trials which found that PNN ablation was effective in alleviating PND symptoms, especially in younger, non-smoking patients.…”
mentioning
confidence: 99%